PENGARUH PELATIHAN KADER JIWA TERHADAP JUMLAH KUNJUNGAN LANSIA DI DESA KARANGBONG KECAMATAN PAJARAKAN KABUPATEN PROBOLINGGO - Isnawati, Iin Aini; Yunita, Rizka (Jurnal Kesehatan Mesencephalon, 2018)
Elderly can cause a person to experience a decrease in physical strength, speed and skills that resulting in a decline of health functions in term of physically, psychologically and socially. This condition causes the elderly to be hampered in carrying out daily activities. As a result, the elderly feel inferior, easily offended, feel useless, unhappy, lose their roles, and are worthless. Efforts to overcome this problem are by forming a mental health cadre so that they can invite the elderly to conduct health check up at the posyandu. This study aims to analyze the effect of soul cadre training toward the number of elderly visits. This study was used experimental quasy design with one group pre-post test design. This research was carried out in Karangbong Village, Pajarakan District, Probolinggo District. The population and sample of this study were all mental health cadresÂ  that is 25 cadre using total sampling. The research instrument was used observation sheets by assessing the number of elderly visits. This study uses data analysis paired t-test. This study shows that there is significant effect of soul cadre training on the number of elderly visits in Karangbong Village, Pajarakan with Ï value of 0,001. Suggestions from this study are that intervention is needed for the elderly such as supportive therapy in order to provide support and motivation to the elderly so that it can improve the quality of lifes welfare physically and psychologically.Â Keywords: training, soul cadre, elderly visit